2016
DOI: 10.18632/oncotarget.13637
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA H19 inhibits autophagy by epigenetically silencing of DIRAS3 in diabetic cardiomyopathy

Abstract: We previously generated a rat model of diabetic cardiomyopathy and found that the expression of long non-coding RNA H19 was downregulated. The present study was aimed to explore the pathogenic role of H19 in the development of diabetic cardiomyopathy. Overexpression of H19 in diabetic rats attenuated cardiomyocyte autophagy and improved left ventricular function. High glucose was found to reduce H19 expression and increase autophagy in cultured neonatal cardiomyocytes. The results of RNA-binding protein immuno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
106
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 121 publications
(112 citation statements)
references
References 25 publications
3
106
0
Order By: Relevance
“…Specific roles of H19 in tumourigenesis are disputable as it harbours pro-tumourigenic [22] and tumour-suppressive [21,23] properties. In diabetes, exposure to high glucose levels reduced H19 expression in neonatal cardiomyocytes, and in the myocardium of streptozotocin (STZ)-induced diabetes in rats used as a model of diabetes [24]. H19 has also been shown to alter the microRNA (miR)-200 pathway by increasing upstream histone acetylation, thus reversing EMT [23].…”
Section: Introductionmentioning
confidence: 99%
“…Specific roles of H19 in tumourigenesis are disputable as it harbours pro-tumourigenic [22] and tumour-suppressive [21,23] properties. In diabetes, exposure to high glucose levels reduced H19 expression in neonatal cardiomyocytes, and in the myocardium of streptozotocin (STZ)-induced diabetes in rats used as a model of diabetes [24]. H19 has also been shown to alter the microRNA (miR)-200 pathway by increasing upstream histone acetylation, thus reversing EMT [23].…”
Section: Introductionmentioning
confidence: 99%
“…Zhang et al also found that the expression of lncRNA MALAT1 was increased dramatically in DCM rat cardiomyocytes and was closely related to its cardiac contractile function . The study of Zhuo et al showed that lncRNA H19 could silence DIRAS3 epigenetically and inhibit autophagy in diabetic cardiomyocytes . Zhang's team study showed that by inhibiting lncRNA‐AK081284, interleukin‐17 ablation reduced cardiac interstitial fibrosis and improved cardiac function in diabetic mice .…”
Section: Long Noncoding Rnasmentioning
confidence: 98%
“…68 The study of Zhuo et al showed that lncRNA H19 could silence DIRAS3 epigenetically and inhibit autophagy in diabetic cardiomyocytes. 69 Zhang's team study showed that by inhibiting lncRNA-AK081284, interleukin-17 ablation reduced cardiac interstitial fibrosis and improved cardiac function in diabetic mice. 4 Gonzalo-Calvo et al indicated that lncRNAs are independent predictors of diastolic function and remodelling in patients with type 2 diabetes.…”
Section: Long Noncoding Rnasmentioning
confidence: 99%
“…LncRNAs have been reported to be associated with the development of various cancers (7,14,19,20). To identify lncRNAs that are involved in the development of ATL, we first examined the expression of selected onco-lncRNAs in HTLV-1-infected cell lines.…”
Section: Lncrna Anril Is Up-regulated In Atlmentioning
confidence: 99%
“…PRC2 has been demonstrated to be a functional target of some lncRNA, e.g., ANRIL, HOTAIR, Fendrr, H19, MALAT1, and COLDAIR (14,15,(17)(18)(19)(20)(21). Moreover, PRC2/lncRNA complex-mediated dynamic control of H3K27 trimethylation (H3K27me3) is central to gene silencing in various cellular processes (8,22).…”
Section: Introductionmentioning
confidence: 99%